2017
DOI: 10.1371/journal.pone.0183586
|View full text |Cite
|
Sign up to set email alerts
|

Treatment effects between monotherapy of donepezil versus combination with memantine for Alzheimer disease: A meta-analysis

Abstract: BackgroundThis is the first meta-analysis to compare the treatment effects and safety of administering donepezil alone versus a combination of memantine and donepezil to treat patients with moderate to severe Alzheimer Disease, particularly regarding cognitive functions, behavioral and psychological symptoms in dementia (BPSD), and global functions.MethodsPubMed, Medline, Embase, PsycINFO, and Cochrane databases were used to search for English and non-English articles for inclusion in the meta-analysis to eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
1
5

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(50 citation statements)
references
References 28 publications
(41 reference statements)
0
44
1
5
Order By: Relevance
“…Previous studies have also indicated that when the course of the disease progresses to moderate or severe levels, combination treatments are more effective than single treatment for delaying the degradation of cognitive functions [12,14,[15][16][17][18][19][20][21][22]. Further, we have reported that memantine administered to patients with moderate to severe AD may inhibit the reduction of cerebral blood flow in the prefrontal area, improve global clinical symptoms, cognitive function and BPSD, and lighten the burden of care placed on caretakers [23].…”
Section: Research Rei Wakementioning
confidence: 83%
See 4 more Smart Citations
“…Previous studies have also indicated that when the course of the disease progresses to moderate or severe levels, combination treatments are more effective than single treatment for delaying the degradation of cognitive functions [12,14,[15][16][17][18][19][20][21][22]. Further, we have reported that memantine administered to patients with moderate to severe AD may inhibit the reduction of cerebral blood flow in the prefrontal area, improve global clinical symptoms, cognitive function and BPSD, and lighten the burden of care placed on caretakers [23].…”
Section: Research Rei Wakementioning
confidence: 83%
“…In the evaluation of global symptoms, there was a significant interaction between the Control and Combination groups in CGI-I (F = 37.67 (1,22), p < 0.001). Regarding cognitive function, there was significant interaction between the Combination group and the Control group in MMSE (F = 9.39 (1,22), p = 0.01) and in CDT (F = 15.84 (1,22), p < 0.001) (Figure 2).…”
Section: Combinational Effect Of Memantine On Global Symptoms and Cogmentioning
confidence: 97%
See 3 more Smart Citations